2012
DOI: 10.2190/om.64.1.c
|View full text |Cite
|
Sign up to set email alerts
|

“Almost the Copy of My Child That'S Dead”: Shakespeare and the Loss of Hamnet

Abstract: This article emphasizes the importance of studies which look at changes and similarities in mourning over time. It argues that relevant evidence can come from creative fiction as well as from other sources, provided that this is analyzed rigorously in terms of structures and patterns. As an illustration of this approach, it examines the evidence in recurring features of Shakespeare's plays that his writing was deeply and lastingly affected by the death of his only son Hamnet, a twin, at the age of 11, and iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
(14 reference statements)
0
2
0
Order By: Relevance
“…René Weis (2007) has pointed to the parallel between the burial of Shakespeare’s son and the descriptions of the Capulets’ tomb in Romeo and Juliet , written shortly after his death. Keverne Smith (2011a, 2011b) and Richard Wheeler (2000) have noted echoes of Shakespeare’s grief in the many father–son relationships in the histories as well as the androgynous young women in the comedies. Rosalind, Portia, and Viola transform themselves from female to male characters, adopting male identities and wearing men’s clothing, perhaps even, as Wheeler suggests, expressing “a father’s fantasy of transforming the surviving daughter into the lost son” (2000, p. 146).…”
Section: The Biographical Context: Shakespeare’s Losses and Complicatmentioning
confidence: 99%
See 1 more Smart Citation
“…René Weis (2007) has pointed to the parallel between the burial of Shakespeare’s son and the descriptions of the Capulets’ tomb in Romeo and Juliet , written shortly after his death. Keverne Smith (2011a, 2011b) and Richard Wheeler (2000) have noted echoes of Shakespeare’s grief in the many father–son relationships in the histories as well as the androgynous young women in the comedies. Rosalind, Portia, and Viola transform themselves from female to male characters, adopting male identities and wearing men’s clothing, perhaps even, as Wheeler suggests, expressing “a father’s fantasy of transforming the surviving daughter into the lost son” (2000, p. 146).…”
Section: The Biographical Context: Shakespeare’s Losses and Complicatmentioning
confidence: 99%
“…In the years between 1602 and 1607, Shakespeare produced all of his major tragedies: Hamlet in 1602, followed by Othello (1604), King Lear (1605), Macbeth (1606), and Antony and Cleopatra (1607). Recent biographical studies have suggested that the plays were influenced by Shakespeare’s traumatic loss of his only son in 1596 and the death of his father in 1601 (Greenblatt, 2004; Honan, 1998; Smith, 2011a, 2011b; Weis, 2007; Wheeler, 2000). This article takes a deeper look at how, in writing Hamlet , Shakespeare may have begun working through his grief in a process of dramatic self-disclosure that informed his major tragedies with enduring emotional depth.…”
mentioning
confidence: 99%